PERANCANGAN DAN IMPLEMENTASI SISTEM MEJA GAMBAR DENGAN METODE XY-TABLE 2 SUMBU MENGGUNAKAN MOTOR STEPPER DAN EMC - Jimmy Linggarjati; Arif Aldiansyah; Daniel Sutanto; Otto Hidayat Imanullah (CommIT Journal, 2007)
The objective of the research was to produce a drawing table system with 2-aksis XY-table method and EMC software implementation. The EMC (Enhanced Machine Control) features are integrated with L297 and L298 as a motor stepper driver to draw simple objects. Methods used in the research are library research, engineering, and laboratory. The results concluded that system can work properly to draw objects such as square, triangle, circle, and capital letters A-Z according to the given input.